Bacteria Associated with the Tannery Effluent and their Alkaline Protease Activities (Plant Tissue Culture and Biotechnology, 2012)
Samples collected from different stages of the tannery processing were found to be alkaline. A good number of bacteria were found to be associated with the different stages of leather processing. The aerobic heterotrophic bacterial count ranged in between 11.9 × 106 and 46.7 × 106. The highest count was observed in the soaking stage and the minimum was found with the bating stage. Among 40 isolates, 31 showed positive proteolytic activities on different protein based media. Identified organisms were Bacillus subtilis (9), B. licheniformis (6), B. alcalophilus (2), B. badius (2), B. cereus (2), B. circulans (2), B. pumilus (2), B. alvei (1), B. brevis (1), B. coagulans (1), B. megaterium (1), B. polymyxa (1) and Micrococcus varians (1). Proteolytic activity was measured as zone ratio on skim milk agar which was found to be in between 1.5 and 5.8. Higher zone ratio was observed in B. subtilis (TS/1/E), B. pumilus (TS/1/S1/A3 and TD/S2/C3), B. licheniformis (TS/1/Q) and B.  badius (TD/21-D). The alkaline protease production by the nine selected isolates ranged in between 7.1 and 119.3 U/ml. Two isolates of B. pumilus (TS/1/S1/A3 and TD/S2/C3) were found to be good alkaline protease producers (119.3 and 94.8 U/ml) among the tested organisms. Biotechnologically these two isolates or their enzymes could be utilized in the tannery industry.   Key words: Bacteria, tannery, effluent, alkaline protease   D. O. I. 10.3329/ptcb.v21i1.9563   Plant Tissue Cult. & Biotech. 21(1): 53-61, 2011 (June)